School Leadership Practices and Internal Efficiency in Secondary Education under Armed Conflict Conditions - Nji, Genevarius (Magister Administrasi Pendidikan, Universitas Muhammadiyah Kendari, 2025)
The main objective of this study was to explore secondary school leadership practices as determinants of internal efficiency in armed conflict areas in selected schools in Bamenda centre, Cameroon. Internal efficiency is a salient aspect in the education production function which if not carefully enhanced by school leadership will engender wastage of scarce available resources. Within the context of this research, school internal efficiency was studied ascertaining a link to leadership practices such as instructional supervision, teacher motivation and financial management. The quantitative approach was adopted for research design. Using the proportionate and purposive sampling techniques, 187 teachers and 80 school administrators were selected for the study. The questionnaire was the instrument used in data collection. The data collected was analysed using regression analysis and the following results were found. It was found that instructional supervision, teachers’ motivation, and financial management of the school principal significantly predict school internal efficiency in secondary schools in armed conflict zones. From this it was concluded that school leadership practices are determinants of internal efficiency in armed conflict areas in selected schools in Bamenda centre. Recommendations were made to stake holders concerned.